Pediatric Lopography Radiographic Examination In A Pre-Stoma Closure (Ileostomy) Case At The Radiology Department Of Rsud Dr. Soeselo Of Tegal Regency - Hikmatul Insani; Retno Wati; Muhammad Za'im (Bajang Institute, 2026)
Background: Lopography is a radiographic examination performed to evaluate bowel conditions prior to stoma closure surgery. Previous studies have reported the use of water-soluble contrast media with anteroposterior (AP), lateral, and oblique projections, with contrast administered through the stoma. However, at the Radiology Department of RSUD (Regional General Hospital) dr. Soeselo of Tegal Regency, pediatric lopography for pre-stoma closure (ileostomy) cases is performed using barium contrast media, an AP projection, and contrast administration through both the stoma and anus. This study aims to determine the examination procedure, the rationale for using barium contrast media, and the reason for utilizing only the AP projection. Methods: This study employed a qualitative method with a case study approach conducted at the Radiology Department of RSUD dr. Soeselo, Tegal Regency, from October 2025 to April 2026. The study subjects consisted of three radiographers and one radiologist. Data were collected through observation, interviews, and documentation. The data were analyzed narratively through transcription, data reduction, comparison with theoretical references, and conclusion drawing. Results: The lopography examination was performed without special preparation other than cleaning the stoma area and removing metallic objects around the abdomen. Equipment and materials prepared included a CR X-ray unit, radiography computer, image reader, radiographic printer, a 34 × 43 cm cassette, a size 16 catheter, 110 grams of barium sulfate contrast mixed with 890 mL of warm water at a ratio of 1:8, a bowl, a 50 cc syringe, a clamp, markers, adhesive tape, gloves, and gel (jelly). The examination was conducted using an AP projection with the patient in a supine position. Barium contrast was administered gradually through the proximal stoma, distal stoma, and anus. Barium contrast was selected because it provides clearer visualization of the intestinal mucosa and anatomy compared with iodinated contrast media. The use of only the AP projection was considered sufficient to demonstrate the entire anatomy of the large intestine, from the ascending colon to the rectum. Conclusion: Pediatric lopography radiographic examination in pre-stoma closure (ileostomy) cases using an AP projection with barium contrast administered through the stoma and anus provides clear visualization of intestinal anatomy, demonstrates contrast distribution throughout the colon, and assists in evaluating bowel conditions before stoma closure surgery. The use of additional projections and watersoluble contrast media may be considered to complement anatomical information and enhance patient safety.